Synergies between critical success factors of Lean Six Sigma and public values - Juliani, Fernando; Oliveira, Otávio José de (Taylor & Francis, 2017)
The purpose of this paper is to identify synergies between the relevant critical success factors (CSFs) of Lean Six Sigma (LSS) and the public values (PVs) introduced into public service management. Firstly, the approach taken by authors in presenting research was to analyse recent literature review emphasizing on the relevant CSFs for LSS application and PVs introduced into public service management. Afterwards, a new analysis highlighting the synergies between these two approaches was performed. Based on the nine more relevant CSFs for LSS application and the seven PV dimensions, five significant synergies between the two approaches were identified in the recent literature. The presenting research should assist public managers of adopting the LSS practice, and guide researchers in the development of surveys aimed at the application of this methodology in public organisations in general, enabling a better quality of services provided to citizens.
Keywords: critical success factors; Lean Six Sigma; public service management; public values; synergies